ACTIVATION OF SEPARATION OF TECHNOLOGICAL MASS ON SEPARATING WORKING SURFACE - Tkachuk , V.S.; Devin , V.V.; Burdeha , V.Yu. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
About 1 thousand tons of soil from each hectare gets into the machine in terms of digging the technologic masses. The process of separation is complicated by the fact that technologic mass contains only 1.5 ... 5% of useful products, and by the fact that the properties of the soil are not permanent, and useful products are sensitive to damage. The process of separation of useful products from soil is determined by breaking lumps and cribbling them through the "live" section of separation working surface. The aim of the study is the productivization of assembling machines, reducing the utility products damage due to the intense flowing of the secondary separation of technologic masses. To activate the process of crushing lumps we must transverse the vibrations of separator. "Single" acts, "earth-ball-bar", "earth-ball-earth-ball”, “earth-ball -useful products" and were considered in the study. It is clear that in a real situation single acts of interaction are not enough to accurately describe the whole process of separation. So we should apply some integrated approaches that would average some physical and mechanical properties of the mixture. The results of the study show: the increasing the efficiency of soil separation with the help of using the separator with transverse vibrations of the separator and the placing the separator flat surface at an angle to the surface of the field is possible; theoretically coboumdary parameters on the basis of circumstantial factors, frequency and amplitude of fluctuations (w = 10. 25 Hz, = 6. 18 mm), the angle of the separator flat surface in the longitudinal direction and speed of aggregate units (supply of technologic mass) are determined by the conditions of optimum separator load (a = 5. 15 deg, v = 0.45. 1.15 m/s).